Assessment of Noninvasive Markers of Steatosis and Liver Fibrosis in Human Immunodeficiency Virus-Monoinfected Patients on Stable Antiretroviral Regimens. (9th June 2022) - Busca, C; Sánchez-Conde, M; Rico, M; Rosas, M; Valencia, E; Moreno, A; Moreno, V; Martín-Carbonero, L; Moreno, S; Pérez-Valero, I; Bernardino, J I; Arribas, J R; et al.
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is a major nonacquired immune deficiency syndrome-defining condition for persons with human immunodeficiency virus (PWH). We aimed to validate noninvasive tests for the diagnosis of NAFLD in PWH. Methods: This is a cross-sectional study of PWH on stable antiretroviral therapy with persistently elevated transaminases and no known liver disease. The area under the receiver operating characteristic curve (AUROC) was calculated to compare the diagnostic accuracy of liver biopsy with abdominal ultrasound, transient elastography (TE) (including controlled attenuation parameter [CAP]), and noninvasive markers of steatosis (triglyceride and glucose index [TyG], hepatic steatosis index [HSI], fatty liver index [FLI]) and fibrosis ([FIB]-4, aminotransferase-to-platelet ratio index [APRI], NAFLD fibrosis score). We developed a diagnostic algorithm with serial combinations of markers. Results: Of 146 patients with increased transaminase levels, 69 underwent liver biopsy (90% steatosis, 61% steatohepatitis, and 4% F ≥3). The AUROC for steatosis was as follows: ultrasound, 0.90 (0.75–1); CAP, 0.94 (0.88–1); FLI, 0.81 (0.58–1); HSI, 0.74 (0.62–0.87); and TyG, 0.75 (0.49–1). For liver fibrosis ≥F3, the AUROC for TE, APRI, FIB-4, and NAFLD fibrosis score was 0.92 (0.82–1), 0.96 (0.90–1), 0.97 (0.93–1), and 0.85 (0.68–1). Optimal diagnostic performance for liver steatosis was for 2 noninvasive combined models of tests with TyG and FLI/HSI as the first tests and ultrasound or CAP as the second tests: AUROC = 0.99 (0.97–1, P < .001) and 0.92 (0.77–1, P < .001). Conclusions: Ultrasound and CAP performed best in diagnosing liver steatosis, and FLI, TyG, and HSI performed well. We propose an easy-to-implement algorithm with TyG or FLI as the first test and ultrasound or CAP as the second test to accurately diagnose or exclude NAFLD. Abstract : An easy-to-implement algorithm diminishes diagnostic uncertainty and the likelihood of diagnostic errors, thus eventually reducing the need for liver biopsy. Ultrasound and controlled attenuation parameter perform very well in diagnosing liver steatosis in persons with HIV.